ISLAMIC ECONOMIC DEVELOPMENT IN INDONESIA THROUGH THE IMPLEMENTATION OF SHARIA FINTECH - Muchlis Bahar (LPPM STIE Muhammadiah Bandung, 2022)
The existence of technological developments strongly influences community life in Indonesia. On the economic side, the presence of sharia fintech will make it easier for the Indonesian people to have funds in emergencies easily and quickly. The purpose of carrying out this research is to be able to analyze how the development of sharia fintech in terms of Islamic economic law in Indonesia. This research will be conducted utilizing a qualitative methodology. The data used in this study originated from a variety of still-relevant prior studies. The conclusion that has been found in this study is that Islamic economic law has a developmental position that is parallel to other conventional economic laws. As for the implementation of sharia fintech, there are conveniences that borrowers will accept, such as no need to meet face to face and easy fulfillment of financial requirements following Islamic economic law.